Anonymous and expeditious mobile user authentication scheme for GLOMONET environments. (7th November 2017) - Gope, Prosanta; Islam, SK Hafizul; Obaidat, Mohammad S.; Amin, Ruhul; Vijayakumar, Pandi
Summary: The Global Mobility Network (GLOMONET) is rapidly becoming important as well as a popular feature in today's high‐performance network. The legal mobile users enjoy life using the ubiquitous services via GLOMONET. However, because of the broadcast nature of the wireless channel, providing user authentication along with the privacy and anonymity of the users in GLOMONET is indeed a challenging task. In this article, we come up with a secure and expeditious mobile communication environment using symmetric key cryptosystem to ensure mobile users' anonymity and privacy against eavesdroppers and backward/forward secrecy of the session key. Our scheme can also protect numerous security threats, like man‐in‐the‐middle attack, known session key attack, lost smartcard attack, and forgery attack. Furthermore, we put forward a new technique named as "friendly foreign agent policy, " where many foreign agents can make different groups among themselves and perform important responsibilities to authenticate a legitimate mobile user without interfering his or her home agent even though the mobile user moves to a new location, covered by a new foreign agent (belongs to the same group). Security and performance analyses show that the proposed scheme is secure and more efficient as compared with other competitive schemes for GLOMONET environments. Abstract : We proposed a secure and expeditious mobile communication system for GLOMONET. Our scheme provides mobile users' anonymity and privacy against eavesdroppers. Our scheme resists other attacks and provides necessary functionalities for mobile users. Our scheme is secure and more efficient as compared to other competitive schemes.